Evaluating shifts in species distribution following herbicide and fertilizer applications for smutgrass (Sporobolus indicus) control in bahiagrass - Nicholas J. Shay; Lisa L. Baxter; Nicholas T. Basinger; William G. Secor; Justin C. Burt; Guy A. Hancock; Brian M. Schwartz; Jason Belcher (Weed Technology)
Novel management strategies for controlling smutgrass have potential to influence sward dynamics in bahiagrass forage systems. This experiment evaluated population shifts in bahiagrass forage following implementation of integrated herbicide and fertilizer management plans for controlling smutgrass. Herbicide treatments included indaziflam applied PRE, hexazinone applied POST, a combination of PRE + POST herbicides, and a nonsprayed control. Fertilizer treatments included nitrogen, nitrogen + potassium, and an unfertilized control. The POST treatment reduced smutgrass coverage regardless of PRE or fertilizer application by the end of the first season and remained low for the 3-yr duration of the experiment (P < 0.01). All treatments, including nontreated controls, reduced smutgrass coverage during year 3 (P < 0.05), indicating that routine harvesting to remove the biomass reduced smutgrass coverage. Bahiagrass cover increased at the end of year 1 with POST treatment (P < 0.01), but only the POST + fertilizer treatment maintained greater bahiagrass coverage than the nontreated control by the end of year 3 (P < 0.05). Expenses associated with the POST + fertilizer treatment totaled US$348 ha−1 across the 3-yr experiment. Other smutgrass control options could include complete removal of biomass (hay production) and pasture renovation, which can cost 3-fold or greater more than POST + fertilizer treatment. Complete removal of biomass may reduce smutgrass coverage by removing mature seedheads, but at a much greater expense of US$2,835 to US$5,825 ha−1, depending on herbicide and fertilizer inputs. Bahiagrass renovation is US$826 ha−1 in establishment costs alone. When pasture production expenses are included for two seasons postrenovation, the total increases to US$1,120 ha−1 across three seasons. The importance of hexazinone and fertilizer as components of smutgrass control in bahiagrass forage was confirmed in this study. Future research should focus on the biology of smutgrass and the role of a PRE treatment in a long-term, larger-scale forage system.